2000
DOI: 10.1016/s0092-8674(00)81558-5
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Inhibits Bone Formation through a Hypothalamic Relay

Abstract: Gonadal failure induces bone loss while obesity prevents it. This raises the possibility that bone mass, body weight, and gonadal function are regulated by common pathways. To test this hypothesis, we studied leptin-deficient and leptin receptor-deficient mice that are obese and hypogonadic. Both mutant mice have an increased bone formation leading to high bone mass despite hypogonadism and hypercortisolism. This phenotype is dominant, independent of the presence of fat, and specific for the absence of leptin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

73
1,496
24
65

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,947 publications
(1,658 citation statements)
references
References 44 publications
73
1,496
24
65
Order By: Relevance
“…7 Although leptin's major role seems to be in the regulation of body weight and energy metabolism, several evidences suggest that this hormone could be involved in other pathophysiological mechanisms, such as immune function, angiogenesis, bone formation and fertility, and the expression of leptin receptor has been demonstrated in a variety of tissues. [8][9][10][11][12][13] The long form of leptin receptor (ObRb) has been found on platelet membrane, 14 and it has been demonstrated that leptin-deficient ob/ob mice, 15,16 and wild-type mice treated with a leptin-neutralizing antibody, 17 develop unstable thrombi and an attenuated thrombotic response to arterial injury, and they exhibit a defective platelet aggregation. Leptin also promotes thrombosis in the mouse, and it potentiates the aggregation of murine platelets in vitro in a leptin receptor-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although leptin's major role seems to be in the regulation of body weight and energy metabolism, several evidences suggest that this hormone could be involved in other pathophysiological mechanisms, such as immune function, angiogenesis, bone formation and fertility, and the expression of leptin receptor has been demonstrated in a variety of tissues. [8][9][10][11][12][13] The long form of leptin receptor (ObRb) has been found on platelet membrane, 14 and it has been demonstrated that leptin-deficient ob/ob mice, 15,16 and wild-type mice treated with a leptin-neutralizing antibody, 17 develop unstable thrombi and an attenuated thrombotic response to arterial injury, and they exhibit a defective platelet aggregation. Leptin also promotes thrombosis in the mouse, and it potentiates the aggregation of murine platelets in vitro in a leptin receptor-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, leptin not only regulates body mass, but also -and at much lower serum concentrations -has an inhibitory effect on bone mass. This effect is apparently not mediated via a direct effect on bone cells and is also independent of endocrine organs such as the pituitary gland, the parathyroid, or adrenal glands, but rather suggests an additional control of bone mass solely by the central nervous system [17].…”
Section: Systemic Regulation Of Bone Remodelingmentioning
confidence: 94%
“…Activation of this receptor suppresses the key transcription factor, ATF4, while it enhances RANKL production. (43)(44)(45) In contrast, genetically manipulated mice with adipocytespecific expression of FoxC2 transcription factor, which increases sensitivity to the beta-adrenergic-cAMP-protein kinase (PKA) signaling pathway, (46) are characterized by high bone mass and conversion of epididymal WAT to beige fat, and beiging of marrow adipocytes. A secretome of beige adipocytes overexpressing FoxC2 includes bone anabolic Wnt10b, IGFBP2, and IGF-1 proteins.…”
Section: Preclinical Insightsmentioning
confidence: 99%
“…Activation of this receptor suppresses the key transcription factor, ATF4, while it enhances RANKL production. (43)(44)(45) …”
mentioning
confidence: 99%